Candida lipolytica Bloodstream Infection in an Adult Patient with COVID-19 and Alcohol Use Disorder: A Unique Case and a Systematic Review of the Literature - Omar Simonetti; Verena Zerbato; Sara Sincovich; Lavinia Cosimi; Francesca Zorat; Venera Costantino; Manuela Di Santolo; Marina Busetti; Stefano Di Bella; Luigi Principe; Roberto Luzzati (MDPI AG, 2023)
Candida lipolytica is an uncommon Candida species causing invasive fungemia. This yeast is mainly associated with the colonisation of intravascular catheters, complicated intra-abdominal infections, and infections in the paediatric population. Here, we report a case of C. lipolytica bloodstream infection in a 53-year-old man. He was admitted for an alcohol withdrawal syndrome and mild COVID-19. Among the primary risk factors for candidemia, only the use of broad-spectrum antimicrobials was reported. The empiric treatment was commenced with caspofungin and then targeted with intravenous fluconazole. Infective endocarditis was ruled out using echocardiography, and PET/TC was negative for other deep-seated foci of fungal infection. The patient was discharged after blood culture clearance and clinical healing. To the best of our knowledge, this is the first case of C. lipolytica candidemia in a patient with COVID-19 and alcohol use disorder. We performed a systematic review of bloodstream infections caused by C. lipolytica. Clinicians should be aware of the possibility of C. lipolytica bloodstream infections in patients with alcohol use disorder, especially in a COVID-19 setting.